UJI COBA MESIN KABEL LAYANG EXPO-2000 GENERASI-II DENGAN KONSTRUKSI DUA GIGI EKSENTRIK TERPISAH UNTUK EKSTRAKSI KAYU - Wesman Endom (Jurnal Penelitian Hasil Hutan, 2014)
Studies of timber extraction was carried out in steep areas by using the prototype Expo-2000 Generation II withengine of 13 HP. Cable line stretching of about 400 m with slope of about 50%. Logs of rasamala of 2-4 m length anddiameter ranged of 20-40 cm were extracted to landing around a tower. The machine was placed on the hill located in themiddle of two cable stretches.The first cable stretch was used for pulling logs upward and the second cable stretch for pullingdownward. The cost for machine investment was about Rp 110 millions with operation costs of Rp 111.975 /hour. Logsextraction productivity is 0.59 m /hour, and the extraction cost was about Rp 189,788 per m .